2013
DOI: 10.1051/m2an/2012057
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modelling of image-based patient-specific blood vessels: zero-pressure geometry andin vivostress incorporation

Abstract: Abstract.In vivo visualization of cardiovascular structures is possible using medical images. However, one has to realize that the resulting 3D geometries correspond to in vivo conditions. This entails an internal stress state to be present in the in vivo measured geometry of e.g. a blood vessel due to the presence of the blood pressure. In order to correct for this in vivo stress, this paper presents an inverse method to restore the original zero-pressure geometry of a structure, and to recover the in vivo st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Solid mechanics could provide another approach to explain branch-related ruptures as the mechanical tension exerted on the tunica media is expected to be elevated near branch bifurcations. Both CFD (Computational Fluid Dynamics to simulate the flow field in a model with rigid walls) and CSM (Computational Solid Mechanics to simulate the wall stress without accounting for the fluid domain) have been used to study arterial fluid dynamics [5][6][7][8][9][10][11][12][13] and solid mechanics [14][15][16] in normal [7][8][9][10][11][12][14][15][16] and aneurysmatic [5,6,13] mice. However, the appropriate pressure and shear distribution as a function of time are essential inputs for a correct CSM simulation, while the inclusion of distending walls has been shown to significantly influence the calculated flow field with CFD [17].…”
Section: An Animal-specific Fsi Model Of the Abdominal Aorta In Anestmentioning
confidence: 99%
“…Solid mechanics could provide another approach to explain branch-related ruptures as the mechanical tension exerted on the tunica media is expected to be elevated near branch bifurcations. Both CFD (Computational Fluid Dynamics to simulate the flow field in a model with rigid walls) and CSM (Computational Solid Mechanics to simulate the wall stress without accounting for the fluid domain) have been used to study arterial fluid dynamics [5][6][7][8][9][10][11][12][13] and solid mechanics [14][15][16] in normal [7][8][9][10][11][12][14][15][16] and aneurysmatic [5,6,13] mice. However, the appropriate pressure and shear distribution as a function of time are essential inputs for a correct CSM simulation, while the inclusion of distending walls has been shown to significantly influence the calculated flow field with CFD [17].…”
Section: An Animal-specific Fsi Model Of the Abdominal Aorta In Anestmentioning
confidence: 99%
“…11,19,22,43 The method is fully implicit thus achieving quadratic convergence, while simulations require very few load steps to reach final solution compared to explicit solvers, 17 and it can run quickly since no mesh updating is required during the analysis. 2,11 Additionally, the present algorithm ensures convergence using a combination of residual and energy criterion checks. In contrast to this, existing backward incremental methods or pull-back iterative inverse approaches 7,9,33,34 are limited with respect to nodal spatial-location convergence checks.…”
Section: Discussionmentioning
confidence: 99%
“…5a and 5b, it is clearly demonstrated that the presence of the ILT layer can give different aortic-wall reference configuration predictions, hence, significantly affecting subsequent studies in rupture risk assessment and haemodynamic analysis, as also reported by various other investigators. 2,26,40 Breast Deformation…”
Section: Abdominal Aortic Aneurysmmentioning
confidence: 99%
See 2 more Smart Citations